Midwifery Students' Perceptions of Spirituality and Spiritual Care: An Example from Western Turkey - Mermer, Gulengul (Journal of religion and health, 2019)
This cross-sectional study aimed to explore Turkish midwifery students' perceptions of spirituality and spiritual care and to investigate the factors affecting them. Data were collected from 271 students of the Midwifery Department of the High School of Health of a state university in the west of Turkey using the Spirituality and Spiritual Care Rating Scale. A significant difference was found between belief in the need for spiritual care and the practice of spiritual care during midwifery training and the total score on the Spirituality and Spiritual Care Rating Scale, but no significant difference was found between the students' year of class, whether they had heard about spiritual care, and their state of knowledge concerning spiritual care. An increase in awareness, knowledge and skills relating to spirituality and spiritual care on the part of midwifery students, who are the midwives of the future, will allow students to provide spiritual care to their patients after they qualify. For this reason, the education program of midwifery students should be seen from a holistic standpoint in order to develop spiritual care.